General Laws Relating to Incorporated Towns of Indian Territory, at 49, Revised Ordinances of the Town of Checotah, Ordinance No. 16, § 3 (1890) - (:unkn) unknown (My University, 1890)
§For any person to fire or discharge any cannon, gun, fowling piece, pistol or other firearms of any description, or fire or explode any squibs, crackers or other things containing powder or other combustible or explosive material in the limits of the town without permission from the mayor, which permission, when so given, shall limit the time of such firing, and shall be subject to be revoked at any time by the mayor. Provided that it shall not be a violation of this ordinance to sound an alarm of fire by the discharge of firearms
Keywords: DISCHARGE